A review on the right of peaceful assembly in Malaysia / Nur Syahirah Mohd Sani and Umi Nurul Ashikin Ismail - Ismail, Umi Nurul Ashikin; Mohd Sani, Nur Syahirah (Faculty of Law, 2014)
This is a study on The Peaceful Assembly Act 2012 and Section 27 of the Police of the Act 1957 which is completed as a fulfilment of the study of the Bachelor of Laws (Hons). The study concerns mainly analysing on the issue of the power of The Peaceful Assembly Act 2012 in regulating assemblies in Malaysia and the differences between The Peaceful Assembly Act 2012 and Section 27 of the Police Act 1957. This research addressed the issue that the Peaceful Assembly Act 2012 is said to be infringing the citizens' rights in organizing assemblies. This may danger the democracy of people as this research findings contain information that may be influenced by certain political views. The objective of this research is to study the existing law in Malaysia (PAA 2012 and Section 27 of PA1957) in regulating organizers and participant of an assembly in Malaysia that has received tremendous criticism from the public. This research discovers that the structure of the Peaceful Assembly Act has been drafted accordingly and it is suitable to be adopted in Malaysia. However more understanding of the law should be implemented to the public so they will understand the situation of the current law that regulates the organizer and participant of an assembly in Malaysia.